2022
DOI: 10.14336/ad.2021.1215
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Short-Chain Fatty Acids Derived from Gut Microbiota in Alzheimer's Disease

Abstract: Short-chain fatty acids (SCFAs) are important metabolites derived from the gut microbiota through fermentation of dietary fiber. SCFAs participate a number of physiological and pathological processes in the human body, such as host metabolism, immune regulation, appetite regulation. Recent studies on gut-brain interaction have shown that SCFAs are important mediators of gut-brain interactions and are involved in the occurrence and development of many neurodegenerative diseases, including Alzheimer's disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 162 publications
1
23
0
Order By: Relevance
“…Furthermore, recent investigations on the relationship between gut microbiota and cognition, including NCDs related to age, could be reversed by gut flora transplantation. Similarly, such relationship was observed in other diseases ( Boehme et al, 2021 ; Qian et al, 2022 ; Thu Thuy Nguyen and Endres, 2022 ).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, recent investigations on the relationship between gut microbiota and cognition, including NCDs related to age, could be reversed by gut flora transplantation. Similarly, such relationship was observed in other diseases ( Boehme et al, 2021 ; Qian et al, 2022 ; Thu Thuy Nguyen and Endres, 2022 ).…”
Section: Discussionsupporting
confidence: 74%
“…Propionate and butyrate induce neutrophil death in the immune system by inhibiting HDAC via a pathway that does not include GPRs or MAPKs. Furthermore, n-butyrate can modulate macrophage functioning in the intestines via suppressing HDACs rather than by triggering toll-like receptor signaling and induction of GPRs [ 62 ].…”
Section: Neurodegeneration and Associated Diseasesmentioning
confidence: 99%
“…Second, the increase the level of SCFAs derived from gut microbiota. As the main metabolite of gut microbiota, SCFAs have been reported to ameliorate cognitive impairment mediated by a variety of etiologies, including DCI (Lee et al, 2020;Enry et al, 2021;Qian et al, 2021;Zheng et al, 2021). Our previous study also found that ZSWF increased fecal SCFAs levels in DCI mice (unpublished).…”
Section: Discussionmentioning
confidence: 74%